The influence of low-progressive scoliosis and its atlas on selected features of the pelvis and spine among 7-15-year-old youth of both sexes and environments - Mrozkowiak, Mirosław (Journal of Education, Health and Sport, 2023)
The purpose of this study was to demonstrate the significant effect of low-progressive scoliosis and the location of its atlas on the values of selected features describing the pelvis and spine. Material and Methods. The study was carried out in a group of 2,361 subjects aged 7 to 15 years, in 6 semiannual consecutive editions. This allowed to record 16,608 observations of 31 features describing posture by photogrammetric method. Results. Three influential traits were selected for multiple regression analysis with selection of a subset of the optimal set of variables like the deviation of the spinous process to the left or right from the vertical and the location of the atlas of this deviation. Conclusions. (1) The effect of low-progressive scoliosis and its atlas on selected features of the spine and pelvis is multidirectional and varied. (2) Left and right low-progressive scoliosis significantly and positively affects almost all features of the spine and pelvis. Significant negative influence is episodic. The features with a significant relationship are Delta angle, the length of lumbar lordosis and the angle of pelvic torsion to the left and right. (3) The low-progressive scoliosis and its atlas show significant and negative effects on the angle of thoracic kyphosis and the length and height of lumbar lordosis.